STATUS OF DATE PALM (Phoenix dactylifera L.) GENETIC ESOURCES IN NIGERIA: Life Science-Agricultural Science - C. D. ATAGA; A. HAMZA MOHAMMED; A. O. YUSUF (International Journal of Life Science and Pharma Research, 2012)
The current status of date palm (Phoenix dactylifera L.) genetic resources in Nigeria collected from varied eco – geographical systems was catalogued. A total of 387 females and 274 males date palms currently exist from a very large number of accessions collected between 1981 and 1990. These accessions are being maintained in an ex situ field gene banks. A few introductions from Namibia (3) and Israel (45) are part of Nigerian collections.